2023
DOI: 10.3390/plants12051149
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Growth Promoting Microbes Change the Photosynthetic Response to Light Quality in Spinach

Abstract: In this study, the combined effect of plant growth under different light quality and the application of plant-growth-promoting microbes (PGPM) was considered on spinach (Spinacia oleracea L.) to assess the influence of these factors on the photosynthetic performance. To pursue this goal, spinach plants were grown in a growth chamber at two different light quality regimes, full-spectrum white light (W) and red-blue light (RB), with (I) or without (NI) PGPM-based inoculants. Photosynthesis-light response curves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The Fv/Fm ratio was approximately between 0.80 and 0.82. It has been reported that the photosynthetic efficacy of plants reduces when they are exposed to stress conditions such as toxicity (Zhao et al, 2007;Santos et al, 2023;Vitale et al, 2023). Hence, the result of the chlorophyll fluorescence revealed that treatment with MgONPs and MnO 2 NPs positively enhanced the chlorophyll fluorescence parameters of Arabidopsis without toxic effects on the plants.…”
Section: Discussionmentioning
confidence: 94%
“…The Fv/Fm ratio was approximately between 0.80 and 0.82. It has been reported that the photosynthetic efficacy of plants reduces when they are exposed to stress conditions such as toxicity (Zhao et al, 2007;Santos et al, 2023;Vitale et al, 2023). Hence, the result of the chlorophyll fluorescence revealed that treatment with MgONPs and MnO 2 NPs positively enhanced the chlorophyll fluorescence parameters of Arabidopsis without toxic effects on the plants.…”
Section: Discussionmentioning
confidence: 94%
“…Exogenous reactive oxygen species (ROS) scrubbers, such as paclobutrazol (PP333), brassinosteroids (BR-120), and complex alcohols, can effectively mitigate waterlog damage; however, these measures have some limitations in the field [22]. Several studies have been conducted in recent years to improve plant stress resistance by inoculating beneficial microorganisms (BMs), typically plant-growth-promoting rhizobacteria, in plants [23][24][25]. Additionally, the inoculation of Ochrobactrum cytisi IPA7.2 induces salinity and drought-resistance in plants and helps them recover following stress [26].…”
Section: Introductionmentioning
confidence: 99%